Leukaemia Cutis in a Patient with Chronic Myeloid Leukaemia with Blast Crisis - Naher, Shamsun; Hoque, Mohammad Mahfuzul (Journal of Medicine, 2023)
Leukaemia cutis is a rare but important extra-medullary manifestation of Leukaemia. It develops due to the infiltration of neoplastic leukocytes or their precursors into the epidermis, dermis or subcutaneous tissue. Cutaneous presentation of Leukaemia cutis can precede, follow, present simultaneously with or may present in the absence of systemic Leukaemia. Here we present a pictorial of a 30-year-old male patient known to have Chronic Myeloid Leukaemia with blastic transformation to Acute myeloid Leukaemia with multiple cutaneous lesions, diagnosed as Leukaemia cutis. J MEDICINE 2023; 24: 65-66